2006
DOI: 10.1111/j.1532-5415.2006.00788.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Protocol for Capillary Blood Glucose Testing in Nursing Home and Rehabilitation Settings

Abstract: This protocol would be useful in long-term care facilities and in other congregate living settings where patients with diabetes mellitus have staff assisting with their diabetes management. Barriers to successful implementation are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…The heterogeneous sample included articles not described due to limited space in this article; 74–110 however, they are included in the reference list. We were not able to compare and contrast and provide a definitive list of those strategies that should always be considered.…”
Section: Resultsmentioning
confidence: 99%
“…The heterogeneous sample included articles not described due to limited space in this article; 74–110 however, they are included in the reference list. We were not able to compare and contrast and provide a definitive list of those strategies that should always be considered.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have observed inappropriate care to be a consequence of deficiencies in guidelines [ 15 , 19 , 30 ] or formal training in diabetes care for healthcare professionals working in long-term care [ 25 , 29 ]. Accordingly, a need for training in diabetes care has also been pointed out [ 10 , 24 , 25 , 29 , 31 ], highlighting areas such as which signs and symptoms to look for, recognising when to perform a CBGM and managing hypoglycaemia.…”
Section: Discussionmentioning
confidence: 99%
“…For CBGM to be useful, it requires a clear purpose, correct sampling and good analytical performance of the device used, as well as appropriate documentation, interpretation and use of the result. However, studies have reported findings such as: that CBGM is not always performed according to individual needs [ 9 – 11 ]; pathogen transmission due to incorrect sampling [ 12 14 ]; insufficient blood glucose logs [ 15 , 16 ]; uncertainty concerning physician involvement [ 15 ] and actual use of test results [ 17 ]; lack of procedures and inconsistent instructions [ 15 , 18 , 19 ]. In addition, training and guidance about symptoms requiring additional measurements are not always adequate [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…After screening was completed, 20 studies were identified that met the criteria for inclusion in this review of the literature. [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]…”
Section: Search Strategymentioning
confidence: 99%
“…The majority of the studies, 70%, used a retrospective, descriptive review of the resident's rec ords. [13][14][15][16][17][18][19][20][21][22][23]25,27,30 Five studies also used a retrospective review of state or federal databases or claim information to help establish validity and gather additional data. 14,15,18,23,30 Surveys were used by 7 studies 13,[19][20][21]24,29,32 with the majority answered by directors of nursing.…”
Section: Designs Instruments and Validity Assessmentmentioning
confidence: 99%